The Influence of Learning Strategies on Students’ Learning Motivation, Engagement, and Academic Performance in the Context of Online Flipped Teaching - Wu Juan; Wu Lei; Yuan Huanhuan; Yang Dongfang (SAGE Open)
This study elucidates how information processing and self-questioning strategies are used in the context of online flipped teaching. A 6-week quasi experimental study was conducted to investigate online flipped teaching with the goal of exploring the impacts of two learning strategies, that is, annotation-summarizing-questioning (ASQ) and concept mapping-questioning (CMQ), on college students’ online learning motivation, learning engagement, and academic achievement. A total of 36 third-year undergraduate students participated in this study. The findings of this research indicated that while these two strategies did not have significant effects on students’ learning motivation or overall performance in terms of learning engagement, they could improve students’ emotional engagement. Additionally, students who used the ASQ strategy exhibited significantly improved cognitive engagement, and their academic performance was significantly better than that of students who used the CMQ strategy. Both strategies can enhance students’ engagement in the context of online flipped learning, but the ASQ strategy is more effective in promoting academic performance. This study, which is of considerable significance, highlights the learning strategies that influence engagement and academic performance in higher education online learning, and outlines the operational experience for online flipped teaching. Future research directions are also discussed.